Evolution of SARS-CoV-2 from BA.2.86 to JN.1 variations and detection in Bangladesh - Roney, Miah; Mohd Fadhlizil Fasihi, Mohd Aluwi (Springer Nature, 2024)
The SARS-CoV-2 virus caused the COVID-19 pandemic and subsequent worldwide health issues because of the introduction of many subvariants, including Alpha, Beta, Gamma, Delta, Epsilon, Zeta, Eta, Theta, Iota, Kappa, Lambda, Mu, and Omicron (Sheeza et al. 2024). Every variation has its own unique set of challenges. Moreover, the COVID-19 infection induces several cytokines, including TNF, IL-1β, and IL-6, as well as pro-inflammatory chemokines including CCL20, CXCL1, CXCL2, CXCL3, CXCL5, CXCL6, and CXCL16 (Marlia et al. 2024). On the other hand, the SARS-CoV-2 saltation variation BA.2.86 has drawn attention across the world and was immediately identified as a variety under surveillance upon its appearance. BA.2.86 was first discovered in August 2023, is phylogenetically distinct from the circulating SARS-CoV-2 omicron XBB lineages, which include EG.5.1 and HK.3 (Satapathy et al. 2024). The spike protein of BA.2.86 has more than thirty mutations, it has a higher potential for immune evasion than XBB and BA.2. Furthermore, BA.2.86 showed a very high affinity for ACE2 binding but lacked a considerable growth advantage and humoral immune escape, when compared to current dominant variants like EG.5.1 and HK.3 (Yang et al. 2024). The development of BA.2.86 led to the appearance of JN.1 (BA.2.86.1.1) (Pirola) in late 2023 (Kaku et al. 2024; Satapathy et al. 2024). Therefore, natural immunity could be involved in warding off the illness. Herd immunity may be important if JN.1 spreads rapidly because some individuals have not yet gotten their vaccinations. Public awareness of social distance and other personal hygiene measures should also be reemphasized (Marlia et al. 2024).